Chalasmenos I : the late Minoan IIIC settlement house A.2 - Eaby, Melissa Suzanne, 1975- (Prehistory monographs, 2018)
"This is the first volume of the final publication of the Late Minoan IIIC settlement at the site of Chalasmenos, located near Ierapetra in eastern Crete. The site was excavated from 1992-2014, initially as part of a Greek-American project under the direction of Metaxia Tsipopoulou and the late William Coulson. This volume is devoted to House A.2, a two-room structure located on the southwestern edge of the site. The excavation and stratigraphy, architecture, pottery, small finds, and faunal material from the building are presented. House A.2 appears to have been used primarily for domestic purposes, serving as the home of an elite (or prospective elite) family, but it also likely served as a meeting and dining or feasting place on certain occasions."--Provided by publisher.